Evolution of a Pivotal Clinical Study to Evaluate Extracorporeal Photopheresis for Refractory Bronchiolitis Obliterans. Issue 1 (April 2021) - Goldberg, Hilary; Hage, Chadi; , Julia Klesney-Tait; Wille, Keith; Arcasoy, Selim; Yung, Gordon; Hertz, Marshall; Chan, Kevin M.; , Matt Morrell; Vedantham, Suresh; Derfler, Mary Clare; Commean, Paul; et al.
No abstract available